Answer:
{y,z,x} = {1/3,-13/3,1/3}
Explanation:
Step by Step Solution:
More Icon
System of Linear Equations entered :
[1] -2y-3y+z=-6
[2] x+y-z=5
[3] 7x+8y-6z=31
Equations Simplified or Rearranged :
[1] -5y + z = -6
[2] y - z + x = 5
[3] 8y - 6z + 7x = 31
Solve by Substitution :
// Solve equation [2] for the variable x
[2] x = -y + z + 5
// Plug this in for variable x in equation [3]
[3] 8y - 6z + 7•(-y +z +5) = 31
[3] y + z = -4
// Solve equation [3] for the variable z
[3] z = -y - 4
// Plug this in for variable z in equation [1]
[1] -5y + (-y -4) = -6
[1] -6y = -2
// Solve equation [1] for the variable y
[1] 6y = 2
[1] y = 1/3
// By now we know this much :
y = 1/3
z = -y-4
x = -y+z+5
// Use the y value to solve for z
z = -(1/3)-4 = -13/3
// Use the y and z values to solve for x
x = -(1/3)+(-13/3)+5 = 1/3
Solution :
{y,z,x} = {1/3,-13/3,1/3}